2001
DOI: 10.1302/0301-620x.83b4.11522
|View full text |Cite
|
Sign up to set email alerts
|

Conservative <I>versus</I> operative treatment for displaced ankle fractures in patients over 55 years of age

Abstract: Forty-seven patients over the age of 55 years with a displaced fracture of the ankle were entered into a prospective, randomised study in order to compare open reduction and internal fixation with closed treatment in a plaster cast; 36 were reviewed after a mean of 27 months. The outcome was assessed clinically, radiologically and functionally using the Olerud score. The results showed that anatomical reduction was significantly less reliable (p = 0.03) and loss of reduction significantly more common (p = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 15 publications
1
93
2
1
Order By: Relevance
“…23 Only one previously published randomised controlled trial has studied older adults. Makwana et al 29 randomised 43 participants aged 66 years to ORIF or a moulded below-knee plaster cast. The results of the trial indicated that participants undergoing casting were more likely to have an early loss of reduction of the fracture (8/21 casting group and 0/22 ORIF group) and lower patient-reported ankle function.…”
Section: Current Management Of Ankle Fractures In Older Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Only one previously published randomised controlled trial has studied older adults. Makwana et al 29 randomised 43 participants aged 66 years to ORIF or a moulded below-knee plaster cast. The results of the trial indicated that participants undergoing casting were more likely to have an early loss of reduction of the fracture (8/21 casting group and 0/22 ORIF group) and lower patient-reported ankle function.…”
Section: Current Management Of Ankle Fractures In Older Adultsmentioning
confidence: 99%
“…23 A randomised trial in elderly patients with a mean follow-up of 27 months also found negligible incidence beyond 3 months. 29 As published evidence of the long-term complications shows low incidence and no difference between operative and non-operative management, we did not plan to model any long-term differences in complications between ORIF and CCC. Extended follow-up of the AIM trial will provide an opportunity to investigate long-term complication rates following ORIF or CCC.…”
Section: Lifetime Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies comparing the effect of early movement compared to immobilisation and weight bearing versus nonweight bearing, the conclusion is that there is no difference in the final result whichever regime is used [44]- [49].…”
Section: Post-operative Managementmentioning
confidence: 99%
“…in addition, neither system is prognostic; fewer than 10% of studies using the Weber classification and fewer than half of the studies using the Lauge-hansen classification have suggested that these classifications can predict outcome (cedell 1967, eventov et al 1978, hughes et al 1979, beauchamp et al 1983, pettrone et al 1983, bauer et al 1985a, rowley et al 1986, ali et al 1987, bauer et al 1987b, ahl et al1989, broos and bisschop 1991, Makwana et al 2001, Lash et al 2002, egol et al 2004, Michelson et al 2007). …”
Section: Mechanism Of Injury and Classificationmentioning
confidence: 99%